Comparative study of negative pressure wound therapy with moist gauze dressings in the treatment of leg ulcer wounds - J., Sridhar; Varsha, Arla Sai; S., Karthick; P., Ravishankar; ., Shailesh (International Surgery Journal, 2020)
Background: Leg ulcers are one of the most commonly encountered cases in any surgical out-patient department. Causes of leg ulcers vary from traumatic, diabetic, chronic venous insufficiency, trophic, hypertensive, and so on. The purpose of this study is to evaluate the safety and clinical efficacy of negative pressure wound therapy compared with moist gauze dressings to treat foot ulcer wounds. Methods: Patients presenting with leg ulcers to the department of general surgery, VMKVC hospital. 50 randomly selected patients will be assigned to the study group based on their willingness for undergoing topical negative pressure dressing and 50 patients to the moist gauze dressing, control group. Results: Most of the ulcer (45.4%) got healed by secondary intention through VAC. dressing. treating DFU with VAC therapy results in a better graft take rate (p=0.05) when compared to standard wound care. There is a statistically significant association found between interventions and the area of the ulcer on day 28. Conclusions: While moist gauze dressing can be applied to any wound surfaces, vacuum dressing is limited to certain surfaces and certain wounds exposing tendon sheath, blood vessels, bones, aponeurosis cannot be treated by vacuum dressing. The frequency of dressing is lower with continuous vacuum suction dressing, while moist gauze has to be changed twice a day to obtain favorable results.